Business succession from an Islamic accounting perspective - Umar Habibu Umar; Junaidu Muhammad Kurawa (ISRA International Journal of Islamic Finance, 2019)
Purpose: The purpose of this paper is to discuss the inheritance of a business from the Islamic accounting perspective. Design/methodology/approach The paper adapts the relevant provisions of conventional accounting standards and practices that conform to Sharīʿah (Islamic law). In addition, the provisions of the Islamic accounting standard for musharakah (AAOIFI's FAS No. 4) found to be relevant are also adapted. Findings The study shows that the assets of an inherited business should be measured at their fair values and that liabilities and legacies must be deducted therefrom with the view to arriving at the equity (or residue). The equity is then distributed among the heirs based on the sharing ratio established according to the Noble Qurʾān, the Sunnah (the Prophet's way) and Muslim jurists' views. Therefore, the inherited business becomes a family business as each heir is admitted into it. By extension, Islam emphasizes that the business should remain a going concern to generate income to sustain the welfare of the heirs. Research limitations/implications The discussion of the paper is limited to the inheritance of a business and its going concern in line with the Sharīʿah. Practical implications Special attention should be paid to the inherited business to ensure not only its continuity to generate income for the heirs but also that each heir gets a correct share of the equity of the business as regulated by the Sharīʿah. Originality/value This study links Islamic inheritance to the going concern of the business, which from all indications has not been given full consideration by previous studies.
Keywords: 330; Musharakah; AAOIFI; Islamic accounting; Going concern; Family inherited business; Islamic succession